Population and spatial development of settlements in Ljubljana Urban Region after 2002 - Rebernik, Dejan (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2014)
The paper is analysing spatial and population development of settlements in Ljubljana Urban Region after 2002. On the basis of population change we determined the main urbanisation processes in the region. To the end of 1970s fast population growth was due to immigration from rural parts of Slovenia and the rest of Yugoslavia. In the 1980s and 1990s deconcentration of population within the region with intense suburbanisation were the main processes. After 2002 the fastest population growth was in in the rural hinterland. Dispersed settlement pattern with all negative implications of urban sprawl is thus characteristic.
Keywords: demografija; demografski razvoj; demography; Ljubljana; mesta; prostorski razvoj; urbana geografija; urbanizacija